ANALISIS FRAMING PEMBERITAAN BASUKI TJAHAJA PURNAMA (AHOK) PADA PEMILIHAN GUBERNUR DKI JAKARTA 2017 DI MEDIA TEMPO.CO DAN DETIK.COM - Sitompul, Heny N; Nasution, Belli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
PDIP’s decision to carry Ahok showed the long journey of Ahok in Jakarta Governor Election 2017. In reporting of Ahok’s news is the result of framed construction by media’s reporters in accordance with the ideology and policy of Tempo.co and Detik.com. This research was conducted to see how Tempo.co and Detik.co construct Ahok’s news when carried by PDIP and how ideology in the news media. This research aims to determine the construction and the news media in reporting Ahok ideology when carried PDIP in online media Tempo.co and Detik.comThis research is using the qualitative method with data collecting technique are documentation, book study and interview. Subjects of this research are the journalists and the editorial of Detik.com and Tempo.co. Objects of this research are the news about Ahok in Jakarta’s Governor Election 2017 from 20 September until 22 September 2016. Data is analyzed by using framing analysis with Zhongdang Pan and Gerald M.Kosicki’s model.The results of this research indicate that: (1) Detik.com news frame by taking the viewpoint of one of the parties who supporting Ahok, which is PDIP. (2) Tempo.co framing news from the perspective of responses and attitudes in decision of PDIP. (3) The News of Detik.com favoring the PDIP, while Tempo.co news is not balanced because it only uses one interviewees only and there is no element of cover both sideKeyword: Frame Analysis, Construction, Ahok’s News